Incremento de eficiencia en una máquina formadora de envases de vidrío, utilizando herramientas manufactura esbelta y seis sigma - Pérez Narváez, Carlos (2011)
The work presented below is a summary of the activities developed as Leader of the project: "Improving the forming efficiency at 0.3% of a forming machine for glass containers." The idea of this project was born after a company analysis found that this machine had the potential to be one of the best machines in Latin America, but had a low efficiency in the forming area, which is why I was asked to determine and addressing the causes of the problem, by targeting an improvement of 0.3%. To facilitate understanding of the project in the first chapter we review a summary of how to make glass containers and existing processes for manufacturing containers, such as: blow and blow, press and blow, and NNPB. As tools to determine the causes of the problem and solutions were used for tools of Lean Six Sigma, in the second chapter will give an overview of the DMAIC process (Define, Measure, Analyze, Improve, Control) and the various tools used in each stage. In the third chapter will show how the project was developed using LSS, in a didactic way our project will relate to each stage of DMAIC, project definition, measurement of process capability analysis of key factors have greater impact on performance the process, implementing solutions to problems that were identified in the previous stage, and then go to the control stage which helped us to maintain over time the improvements